Management Accounting with a Focus on Macro-Environmental, Professional, and Organizational Factors and the Outcomes of Management Development - Movahedian , Maryam; Piri, Habib; Hirad, Alireza; Sotudeh, Reza (Management Strategies and Engineering Sciences, 2025)
This article aims to explain the development model of the management accounting profession in Iran. To facilitate the advancement of the management accounting profession, experts must pay special attention to the Commercial Code, accounting theory, and accounting analysis, alongside elective options such as trade law, strategy, or control. Many managerial positions require a master's degree, professional certifications, and/or relevant field experience. Based on the aforementioned points, the researcher seeks to formulate a model for the development of the management accounting profession in Iran. Drawing upon a review of prior literature and existing research, the study investigates various barriers to the development model of management accounting. The findings indicate that four primary barriers hinder the application of the management accounting profession based on the professional development theory of management accounting: (1) contextual factors affecting the management accounting profession model based on the type of violation, (2) environmental factors influencing the management accounting profession model, (3) strategies that impact the implementation of the management accounting profession model, and (4) outcome-related consequences of implementing the management accounting profession model.